Development Of An Educational Game For Introducing Indonesian Traditional Musical Instruments Using Construct 2 At Sdn Patra Manggala 2, Tangerang Regency - Bintang Adi Purnama; Abdul Halim; Ali Rohman (ARRUS Journal of Engineering and Technology, 2025)
The rapid development of information technology can be utilized as an engaging and interactive learning medium, especially for elementary school students. One effective way to introduce Indonesian culture from an early age is through digital media that presents traditional musical instruments. This study aims to develop an educational game using Construct 2 as an interactive learning medium to introduce various types of Indonesian traditional musical instruments to fourth-grade students at SDN Patra Manggala 2, Tangerang Regency. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage is conducted to identify the needs of students and teachers, while the design and development stages are used to design and build the educational game. Subsequently, the implementation and evaluation stages are carried out to test the feasibility and effectiveness of the game in the learning process. The test results show that the developed game is rated as "highly feasible" based on validation from media and content experts, and received positive responses from both students and teachers. This game not only provides knowledge about traditional musical instruments but also enhances students' learning motivation through enjoyable visual, audio, and interactive approaches. Therefore, this Construct 2-based educational game can serve as an effective and engaging alternative learning medium to introduce Indonesian culture to elementary school students.